Current challenges and improvements in assessing the immunogenicity of bacterial vaccines - Fantoni, Giulia; Boccadifuoco, Giuseppe; Verdirosa, Federica; Molesti, Eleonora; Manenti, Alessandro; Montomoli, Emanuele (Frontiers in Microbiology, 2024)
The increase in antimicrobial-resistant bacterial strains has highlighted the need for a new vaccine strategy. The primary goal of a candidate vaccine is to prevent disease, by inducing a persistent immunologic memory, through the activation of pathogen-specific immune response. Antibody titer is the main parameter used to assess the immunogenicity of bacterial vaccine candidates and it is the most widely used as a correlate of protection. On the other hand, the antibody titer alone cannot provide complete information on all the activity mediated by antibodies which can only be assessed by functional assays, like the serum bactericidal assay and the opsonophagocytosis assay. However, due to the involvement of many biological factors, these assays are difficult to standardize. Some improvements have been achieved in recent years, but further optimizations are needed to minimize inter-and intra-laboratories variability and to allow the applicability of these functional assays for the vaccine immunogenicity assessment on a larger scale.